2021
DOI: 10.1123/jtpe.2019-0164
|View full text |Cite
|
Sign up to set email alerts
|

Affective Learning in Physical Education: A Systematic Review

Abstract: Purpose: The purpose of this study was to carry out a systematic review of intervention programs that have addressed affective learning outcomes within physical education and to explore pedagogical practices in alignment with teaching, lesson content, and learning outcomes. Method: The literature search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Included were 26 peer-reviewed pedagogical studies of physical education programs that addresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 66 publications
1
28
0
4
Order By: Relevance
“…Furthermore, this finding shows that online interventions have the potential to help practitioners address gaps in their practice to support affective outcomes. Indeed, there has been a growing awareness of the significance of affective outcomes related to youth mental health and wellbeing, but there are few well-established and widely practiced pedagogical approaches that influence students' affective outcomes, with teachers reported to have limited skills and resources to facilitate affective learning (Kirk 2020;Teraoka et al 2020). At the same time, there was not substantial evidence that online interventions supported cognitive and social outcomes, and neither were these domains a central and explicit focus of the interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this finding shows that online interventions have the potential to help practitioners address gaps in their practice to support affective outcomes. Indeed, there has been a growing awareness of the significance of affective outcomes related to youth mental health and wellbeing, but there are few well-established and widely practiced pedagogical approaches that influence students' affective outcomes, with teachers reported to have limited skills and resources to facilitate affective learning (Kirk 2020;Teraoka et al 2020). At the same time, there was not substantial evidence that online interventions supported cognitive and social outcomes, and neither were these domains a central and explicit focus of the interventions.…”
Section: Discussionmentioning
confidence: 99%
“…C (Comparison): no engagement with or use of Online-Based medium; or no comparison (such as in cross-sectional or qualitative research designs) . O (Outcomes): changes to physical activity, including behaviours (physical), knowledge or understanding (cognitive), interactions (social) and attitudes or feelings (affective) (see Table 1 for further examples of the outcomes across the four domains that were included in this review, that were identified from literature that has conceptualised the learning domains in relation to learning outcomes associated with models-based practice, the concept of physical literacy, assessment and previous reviews on learning in physical education and sport pedagogy - (Casey and Goodyear 2015;Dudley, Goodyear, and Baxter 2016;Kirk 2020;Teraoka et al 2020). .…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…An emphasis on PYD and life skill education in sport and physical activity has taken root in community settings such as after-school programs and summer camps (Hellison et al, 2000 ; Gould and Carson, 2008 ; Gordon et al, 2016 ; Holt, 2016 ; Jacobs and Wright, 2018 , 2021 ). However, the PYD framework is not often applied in school-based PE despite its apparent relevance (Wright and Li, 2009 ) and a strong body of literature focused on students' development of personal and social skills within PE (Hemphill et al, 2015 ; Pozo et al, 2016 ; Opstoel et al, 2020 ) as well as their affective development (Teraoka et al, 2020 ). These aspects of PE not only align with PYD outcomes, but also with PE content standards in many nations such as the U.S., New Zealand and Scotland (Richards and Gordon, 2017 ; Wright and Irwin, 2018 ; Wright et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…One way to support progress in this area is to study life skills directly to make an empirical case for PE experiences having the capacity to foster PYD (and hence SEL) outcomes. Valid and reliable methods that examine which life skills students report learning through PE could foster this solution (Pozo et al, 2016 ; Teraoka et al, 2020 ; Dyson et al, 2021 ). In this study we sought to explore how students perceived learning life skills in a PE class taught using a PYD oriented life skill education approach called the Teaching Personal and Social Responsibility model (TPSR; Hellison, 2011 ) compared to students in a class where life skills were not explicitly emphasized.…”
Section: Introductionmentioning
confidence: 99%